Signs of heart failure with preserved ejection fraction in atrial fibrillation patients normalise in many patients after restoration of sinus rhythm. (14th October 2021) - Wagemakers, M.C.P; Wesselink, R; Neefs, J; Kougioumtzoglou, A; Van Den Berg, N.W.E; De Bruin-Bon, R.H.A.C.M; Piersma, F.R; De Jong, J.S.S.G; Van Boven, W.J.P; Driessen, A.H.G; Van Gelder, I.C; De Groot, J.R
Abstract: Background: Atrial fibrillation (AF) and heart failure with preserved ejection fraction (HFpEF) coexist in many patients. AF and HFpEF are closely intertwined, but there are important knowledge gaps in the pathogenesis, risk, prevention and treatment of AF with concomitant HFpEF, in particular with respect to reversal of HFpEF signs. Purpose: To assess the proportion of AF patients with (any) HFpEF criteria (including patients with heart failure with moderately reduced ejection fraction (HFmrEF)) who – after successful AF ablation – no longer meet the criteria for HFpEF on neurohumoral and echocardiographic level. Furthermore, to assess whether normalisation of HFpEF criteria positively affects AF recurrence. Methods: Patients (n=526) underwent thoracoscopic AF ablation, consisting of pulmonary vein isolation (PVI) alone or PVI with additional lines in the case of persistent AF and were prospectively followed-up. Patients (n=338) with a left ventricular ejection fraction (LVEF) ≥40% and a successful ablation at 6 months follow-up, that is freedom of AF, or any atrial tachycardia of more than 30 seconds, were included in this study. Participants were grouped based on N-terminal pro-b type natriuretic peptide (NT-proBNP) into those with a NT-proBNP <125pg/ml, defined as control patients (group 1), and those with a NT-proBNP level ≥125pg/ml, defined as HFpEF patients (group 2). HFpEF patients were further classified in different degrees of HFpEF severity, based on the number of diagnostic echocardiographic criteria for diastolic dysfunction present into possible HFpEF (group 2a, <2 criteria), likely HFpEF (group 2b, 2 criteria) and definite HFpEF (2c, ≥3 criteria). The primary outcome was the change in HFpEF defining signs on neurohumoral (NT-proBNP) level and echocardiographic (number of echocardiographic criteria for diastolic dysfunction) level 6 months after restoration of sinus rhythm. Results: In total, 69% of AF patients (with a preserved ejection fraction of ≥40%) fulfilled the criteria for HFpEF. In 23% of these patients, neurohumoral levels normalised after elimination of AF, and a normalisation of echocardiographic markers was seen in 58% of patients. Normalisation of HFpEF on a neurohumoral level was associated with numerically fewer AF recurrence at 1 year follow-up (23% versus 33% in patients with and without NT-proBNP <125 pg/ml respectively, p=0.212). This favourable outcome was not observed in patients with a normalisation of echocardiographic markers. Conclusion: In AF patients with definite restoration of sinus rhythm HFpEF may be reversed. This suggests that neurohumoral and echographic changes are caused by AF rather than by HFpEF. Normalisation of neurohumoral changes after definite restoration of sinus rhythm led to better outcome with regards to AF-recurrence, which could be used in prediction of prognosis. Funding Acknowledgement: Type of funding sources: None.